Complementary Therapies in Allergic Rhinitis - Sayin, Ibrahim (Hindawi Publishing Corporation, 2013)
Objective. To determine the prevalence of herbal treatment of allergic rhinitis. Methods. In this prospective study, patients who were diagnosed with perennial allergic rhinitis were questioned about their use of natural products/herbal therapies for their symptoms. Results. In total, 230 patients were enrolled. Overall, 37.3% of the patients stated that they had used natural products/herbal therapies at least once. Women were more likely than men to use herbal supplements (38.3% versus 32.4%). Ten different types of herbal supplements were identified, with stinging nettle (Urtica dioicath), black elderberry (Sambucus nigra), and Spirulina being the most common (12.6%, 6.1%, and 5.7%, resp.). Conclusion. This study found a high prevalence of herbal treatment usage for the relief of allergic rhinitis symptoms in Turkey. The herbal products identified in this study and in the literature are discussed.